The role of non-governmental organizations (NGOs) as intermediaries of the European union decision to adopt international accounting standards: 1973-2002 - Kaya, D.; Kirsch, R.J.; Henselmann, K. (Accounting Historians Journal, 2016)
This paper analyzes the role of non-governmental organizations (NGOs) as intermediaries in encouraging the European Union (EU) to adopt International Accounting Standards (IAS). Our analysis begins with the 1973 founding of the International Accounting Standards Committee (IASC), and ends with 2002 when the binding EU regulation was approved. We document the many pathways of interaction between European supranational, governmental bodies and the IASC/IASB, as well as important regional NGOs, such as the Union Européenne des Experts Comptables, Économiques et Financiers (UEC), the Groupe d’Etudes des Experts Comptables de la Communauté Économique Européenne (Groupe d’Etudes), and their successor, the Fédération des Experts Comptables Européens (FEE). This study investigates, through personal interviews of key individuals involved in making the history of the organizations studied, and an extensive set of primary sources, how NGOs filled key roles in the process of harmonization of international accounting standards. © 2016, American Accounting Association. All rights reserved.
6 citations (Crossref) [2023-10-31]
Keywords: dept.acc